Top Incomes in Germany, 1871-2014 - Charlotte Bartels (Institute of Labor Economics (IZA), 2018)
This study provides new evidence on top income shares in Germany from the period of industrialization to the present. Income concentration was high in the nineteenth century, dropped sharply after World War I and during the hyperinflation years of the 1920s, and increased rapidly throughout the Nazi period beginning in the 1930s. Following the end of World War II, German top income shares returned to 1920s levels. The German pattern stands in sharp contrast to developments in France, the UK, and the US, where World War II brought a sizeable and lasting reduction in top income shares. Since the turn of the millennium, income concentration in Germany has been on the rise and is today among the highest in Europe. Regression analysis reveals that rising top income shares are positively associated with the capital share, trade and technological change.
Keywords: D31; D63; J31; N30; 330; welfare state; income inequality; income distribution; top incomes; Germany